Making concrete a temperature sensor - Chu, Fiona (2017)
Thermoelectric behavior refers to the generation of a voltage due to a temperature differential. This has been observed in cementitious materials. This characteristic is useful in cement-based structures as the structure can monitor its own temperature in the event of building fires. However, the cementitious material is vulnerable to fire as it losses its strength under heat and risks spalling. An alternative construction material known as geopolymer has been developed with better fire resistance traits compared to concrete. The thermoelectric behavior of geopolymer has not been investigated so far. Therefore, focus of this study is to discover of the thermoelectric behavior of geopolymer by doing a comparison to strain hardening cementitious composites (SHCC) and cement paste. Additionally, experimental set-ups have been explored to improve the accuracy of voltage and temperature measurements. From the test, it can be observed that the heating and cooling curve of geopolymer displays good linearity and reversibility. High Seebeck has been also discovered in geopolymer when compared to cement paste. Geopolymer has a Seebeck coefficient of 5810 times than plain cement paste, 2540 times than SHCC, 1400 times than carbon fiber reinforced concrete and 30 times than steel fiber reinforced concrete. This shows that geopolymer is a good electron conductor, but a poor thermal conductor.